Development issues for impact safety of rail vehicles: Robustness of crashworthy designs, effect of structural crashworthiness on passenger safety and behaviour characterisation of vehicle materials. (February 2018) - Xue, Xiangdong; Robinson, Mark; Schmid, Felix; Smith, Roderick
This paper supplements two previous papers written by the authors and addresses three issues arising from those papers. The three issues are follows: (1) the robustness of a crashworthy design in scenarios different from the design conditions, (2) the correlation of structural crashworthiness with passenger safety and (3) behaviour characterisation of vehicle materials in train collisions. The investigation of these issues provides an increased understanding of the research conclusions gained from a number of varied conditions, and targeting the development requirements in these three areas will promote crashworthiness applications in rail vehicles.